Russia against the rest the post-Cold War crisis of world order - Sakwa, Richard 1953- (Cambridge University Press, 2017)
In this book Richard Sakwa provides a new analysis of the end of the Cold War and the subsequent failure to create a comprehensive and inclusive peace order in Europe. The end of the Cold War did not create a sustainable peace system. Instead, for a quarter of a century a 'cold peace' reflected the tension between cooperative and competitive behaviour. None of the fundamental problems of European security were resolved, and tensions accumulated. In 2014 the crisis exploded in the form of conflict in Ukraine, provoking what some call a 'new Cold War'. Russia against the Rest challenges the view that this is a replay of the old conflict, explaining how the tensions between Russia and the Atlantic community reflect a global realignment of the international system. Sakwa provides a balanced and carefully researched analysis of the trajectory of European and global politics since the late 1980s